(untitled) (Journal of Hama University, 2019)
The aim of this study is to know the role of financial failure prediction models in the construction of the bank loan portfolio. To achieve this, the models of the most frequent financial failure are applied Altman, Kida and Sherrod on a sample consists of 12 Syrian public and private joint-stock companies during the period 2013-2017. The results of the research show that the ability of the models of financial failure to distinguish between the Syrian companies that are not threatened by the financial failure, which have good financial positions, low degree of risk and can be allocated by the bank in part of the loans, when construction the loan portfolio, and the companies that are threatened with the financial failure, they face a high degree of risk and are not a candidate for loans, when the bank constructa a loan portfolio. The analysis of the comparison between the financial failure prediction models (Altman, Kida, Sherrod) show a difference in the accuracy of the degree of risk and predict the financial failure of the Syrian public and private joint stock companies. The previous models agre to classify FMJ as the worst joint stock company, Sherrod’s model differ with the Altman and Kida models in the company’s best rating, and the results of the comparison of these models according to the exposure to financial failure show that the Sherrod model is the best in classifying the sample and the banks could rely more on the other two models when constructing the loan portfolio.